An examination of climate change impacts on coastal tourism in Durban, South Africa - Mgadle, Aphelele (Vaal University of Technology, 2022)
Coastal communities are facing several environmental and developmental challenges. As the Decade of Sustainable Development Goals Action aimed at ensuring delivery of the aspirations set out in Agenda 2030 draws closer, a parallel initiative has been made on oceans. In 2018 the United Nations launched the Decade of Ocean Science (2021-2030), aimed at exploring the challenges faced by oceans and coastal communities. Given Operations Phakisa's well-documented socio-economic significance of oceans in South Africa, it is crucial to understand how climate change affects the country’s coastal tourism to inform policy and practice going forward. This study examined climate change impacts on coastal tourism in Durban. It used archival data from the National Oceanic and Atmospheric Administration, primary data collected from key informant interviews (n=10), and an online questionnaire (n=302). Data analysis was done using XLSTAT 2021, Mann-Kendall Trend Analysis, Question-Pro Analytics and content and thematic analysis. The study found that extreme weather events such as rising sea levels, increases in tidal activity, coastal flooding and heat waves are identifiable threats to Durban’s future as a tourist destination. The study also found that sea level rise, sea surges, coastal storms, and high tides are worsening the challenge of beach erosion and coastal flooding, threatening tourism infrastructure in the process. In response, the eThekwini Municipality has embarked on response initiatives which include beach nourishment programmes, dune restoration and coastal defence mechanisms to conserve the beachfront and hopefully ensure coastal tourism sustainability. To assist such efforts, this study recommends educational support by civil society and government to sensitise and improve climate change understanding from a tourism perspective to ensure the sector’s adaptation and resilience. It also recommends public-private partnerships for the protection of coastal tourism infrastructure. Lastly, given the apparent threat of sea-level rise along Africa and South Africa’s coastlines, the study advocates a de-risked approach to constructing tourism properties.
MM (TTSM) (Department of Travel and Tourism Services Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Coastal tourism; Sea-level rise; Durban; Sustainability; Climate change; Dissertations, Academic -- South Africa.; Climatic changes -- South Africa.; Tourism -- Environmental aspects.; Coastal zone management -- South Africa.